The Role of Mancala Games in Human Evolution, Cultural Development, and Education: An Anthropological Inquiry - Zhang, Jian; Liu, Yingdan; Yin, Zijun; Abbas, Safdar; Qin , Shengdong (Quality in Sport, 2023)
Mancala games, a diverse category of traditional board games played across cultures worldwide, bear resemblances to chess in their significance to human evolution and cultural progress. Drawing from anthropological investigations, this research uncovers the adaptability of mancala games to farming, marine, and nomadic cultures, tracing their origins to ancient Egypt and their subsequent spread among diverse civilizations in Africa, Malaysia, and China. This study highlights the extensive contributions of mancala games across various educational domains, encompassing moral, intellectual, physical, and aesthetic education, all of which foster comprehensive human development. By examining the cultural, historical, and educational dimensions of mancala games, this research unveils their profound impact on human societies throughout history, shedding light on their enduring significance. Mancala games emerge as powerful tools for promoting moral reasoning, critical thinking abilities, strategic planning skills, physical coordination, and cultural understanding. They embody cultural traditions, transmit ancestral knowledge, and foster social cohesion. Through their entertainment value and ability to shape and enrich human experiences, mancala games weave a cultural tapestry that intertwines with human societies, both past and present.